2020
DOI: 10.1038/s41598-020-70351-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drug metabolizing enzymes and transporters in Thai colorectal cancer patients treated with irinotecan-based chemotherapy

Abstract: Genetic polymorphisms in drug metabolizing enzymes and drug transporters may affect irinotecan toxicity. Although genetic polymorphisms have been shown to influence the irinotecan toxicity, data are limited in Thai population. Thus, the aim of this study was to assess the allele and genotype frequencies and the relationship between CYP3A4/5, DPYD, UGT1A1, ABCB1, and ABCC2 genetic variations and irinotecan-induced toxicity in Thai colorectal cancer patients. One hundred and thirtytwo patients were genotyped, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In the present research, we observe a frequency of 0.36 for UGT1A1*28 , which is comparable to the 0.33 reported in a previous study on the prevalence of Gilbert's syndrome in the Chilean population, and where the presence of the UGT1A1*28 allele was determined indirectly by analyzing the rs6742078 (G > T) variant located in intron 1 of the UGT1A1 gene, which is also in strong linkage disequilibrium with UGT1A1*28 ( Méndez et al, 2013 ). These frequencies are very similar to those described in other Latin American (Colombia: 0.34; Peru: 0.45; Mexico: 0.37) and European (0.30; Project 1000 genomes) populations, but different from Asian populations, where allele frequencies of 0.16 have been reported ( Atasilp et al, 2020 ). The genotype frequencies observed in this study for CYP2B6 c.516G>T (rs3745274) (G/G: 38.81%; G/T: 46.27%; T/T: 14.92%, Table 3 ) were very similar to those of a previous study carried out in a Chilean population under therapy with EFV (G/G: 43%; G/T: 42%; T/T: 15%) ( Carr et al, 2010 ), where the frequency of allele T (0.38) was very similar to that of other Latin American populations such as Colombian (0.37), Mexicans (0.31), and Puerto Rican (0.35), and higher than that described in Europeans (0.24; Project 1000 genomes).…”
Section: Discussionsupporting
confidence: 88%
“…In the present research, we observe a frequency of 0.36 for UGT1A1*28 , which is comparable to the 0.33 reported in a previous study on the prevalence of Gilbert's syndrome in the Chilean population, and where the presence of the UGT1A1*28 allele was determined indirectly by analyzing the rs6742078 (G > T) variant located in intron 1 of the UGT1A1 gene, which is also in strong linkage disequilibrium with UGT1A1*28 ( Méndez et al, 2013 ). These frequencies are very similar to those described in other Latin American (Colombia: 0.34; Peru: 0.45; Mexico: 0.37) and European (0.30; Project 1000 genomes) populations, but different from Asian populations, where allele frequencies of 0.16 have been reported ( Atasilp et al, 2020 ). The genotype frequencies observed in this study for CYP2B6 c.516G>T (rs3745274) (G/G: 38.81%; G/T: 46.27%; T/T: 14.92%, Table 3 ) were very similar to those of a previous study carried out in a Chilean population under therapy with EFV (G/G: 43%; G/T: 42%; T/T: 15%) ( Carr et al, 2010 ), where the frequency of allele T (0.38) was very similar to that of other Latin American populations such as Colombian (0.37), Mexicans (0.31), and Puerto Rican (0.35), and higher than that described in Europeans (0.24; Project 1000 genomes).…”
Section: Discussionsupporting
confidence: 88%
“…4,24,[28][29][30][31][32][33] Several of the most recent studies in Asia have experienced similar results. 17,[34][35][36] The UGT1A1*28 polymorphism has also been reported to be correlated with irinotecan-related diarrhea; however, the conclusions were controversial for neutropenia. The majority of meta-analyses 4,24,[28][29][30][31][32][33] and two recent studies performed in Asia 35,36 concluded that the UGT1A1*28 polymorphism could increase the risk of neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…17,[34][35][36] The UGT1A1*28 polymorphism has also been reported to be correlated with irinotecan-related diarrhea; however, the conclusions were controversial for neutropenia. The majority of meta-analyses 4,24,[28][29][30][31][32][33] and two recent studies performed in Asia 35,36 concluded that the UGT1A1*28 polymorphism could increase the risk of neutropenia. Campbell et al revealed that such an effect was greater than that of neutropenia in both Asian and Caucasian patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood routine examination data, including neutrophil count (cells×10 9 /L), were collected after chemotherapy and at least once per week for three weeks. Neutropenia (neutrophil count < 2×10 9 /L) has been used as an indicator for evaluating toxic effects of chemotherapy in many studies 16–20 according to WHO HANDBOOK FOR REPORTING RESULTS OF CANCER TREATMENT. Following the WHO criteria 21 for myelosuppression, neutropenia signified the neutrophil count is less than 2×10 9 /L.…”
Section: Methodsmentioning
confidence: 99%